2011
DOI: 10.1002/rra.1494
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSING THE IMPACTS OF RIVER REGULATION ON NATIVE BULL TROUT (SALVELINUS CONFLUENTUS) AND WESTSLOPE CUTTHROAT TROUT (ONCORHYNCHUS CLARKII LEWISI) HABITATS IN THE UPPER FLATHEAD RIVER, MONTANA, USA

Abstract: Hungry Horse Dam on the South Fork Flathead River, Montana, USA, has modified the natural flow regimen for power generation, flood risk management and flow augmentation for anadromous fish recovery in the Columbia River. Concern over the detrimental effects of dam operations on native resident fishes prompted research to quantify the impacts of alternative flow management strategies on threatened bull trout (Salvelinus confluentus) and westslope cutthroat trout (Oncorhynchus clarkii lewisi) habitats. Seasonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 103 publications
(89 reference statements)
0
15
0
1
Order By: Relevance
“…We developed habitat time series of WUA for an entire water year (i.e., 2013) based on daily stream flows at the Anderson Ranch gage station, water depth, and velocities in each grid cell and DMT (Benjankar et al, ). Habitat time series has been used in other studies as an indicator for temporal habitat status (Li, Chen, Tonina, & Cai, ; Muhlfeld et al, ). We compared habitat (WUA) and hydraulic‐based habitat (WUA) time series to analyse the effect of temperature on habitat prediction.…”
Section: Methodsmentioning
confidence: 99%
“…We developed habitat time series of WUA for an entire water year (i.e., 2013) based on daily stream flows at the Anderson Ranch gage station, water depth, and velocities in each grid cell and DMT (Benjankar et al, ). Habitat time series has been used in other studies as an indicator for temporal habitat status (Li, Chen, Tonina, & Cai, ; Muhlfeld et al, ). We compared habitat (WUA) and hydraulic‐based habitat (WUA) time series to analyse the effect of temperature on habitat prediction.…”
Section: Methodsmentioning
confidence: 99%
“…However, for the data included in our study, 11% of the Bull Trout observed during snorkel surveys were 400 mm TL or larger. Since Bull Trout of this length are usually considered mature Muhlfeld et al 2012) and since previous population modeling exercises have assumed that about 10% of all Bull Trout in a population are adults (Rieman and McIntyre 1993;Rieman and Allendorf 2001), the proportion of spawning adults among the fish observed during snorkeling was probably similar to the proportion of spawning adults within the actual populations. For this reason, we believe that the use of snorkel data sets in PVAs is appropriate if (1) observation error is not high or (2) observation error is high but the projected extinction risk is low (since, as mentioned above, observation error can only bias the extinction risk upward).…”
Section: Data Limitationsmentioning
confidence: 99%
“…However, an unrelated mark-recapture study conducted in Lake Pend Oreille during 2008 produced an estimate of 12,513 Bull Trout (≥400 mm TL; Hansen, unpublished data). Since 400-mm and larger fish are mostly mature in this population ; also see Muhlfeld et al 2012), we used the latter estimate for adult abundance in the present study. Even the mark-recapture estimate assumes that there is no resident or fluvial component to the population.…”
Section: Data Limitationsmentioning
confidence: 99%
“…Moreover, subadult (<300 mm) bull trout and westslope cutthroat trout emigrate from their natal tributaries primarily in the spring (Fraley & Shepard 1989; Liknes and Graham 1988) and then migrate downriver into lower portions of the Flathead River and Flathead Lake in the spring and autumn (Shepard et al. 1984; Fraley & Shepard 1989; Muhlfeld & Marotz 2005; Muhlfeld et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1). The current flow management strategy mimics the natural spring runoff event, within flood constraints, gradually reducing dam discharge towards stable flows during summer, autumn and winter, which maximises the availability of critical bull trout and westslope cutthroat trout habitats in the dam‐influenced reaches of the mainstem Flathead River (Muhlfeld et al. 2011).…”
Section: Methodsmentioning
confidence: 99%